Branding D'Raja Coffe menjadi HUB D'raja Coffee - Mega Ulva Sari Sihombing; Evi Enitari Napitupulu; Nurhawati Simamora; Novira Sazelika (Universitas Sari Mutiara Indonesia, 2023)
This study aims to analyze the brand changes at D'raja Coffee, where the changes are clearly made starting from the Menu Book and Clothing used by the cafe employees, not only that, in the process the cafe also provides new menus that are no less delicious for cafe visitors because in the process d'raja is also not active in promoting its business, not always using social media such as Instagram but the level of satisfaction and trust of customers who visit the cafe. With this study, the researcher uses Branding theory to see the changes in the cafe logo starting from the menu book and clothing of D'raja cafe employees using qualitative methods and descriptive approaches that explain the process of change using interview techniques along with observation and documentation of the cafe which is associated with data triangulation methods and techniques.